Electronic health records with Epic and IBM FlashSystem 9500 Blueprint version 2, release 4. (IBM Redbooks, 2022)
This information is intended to facilitate the deployment of IBM© FlashSystem© for the Epic Corporation electronic health record (EHR) solution by describing the requirements and specifications for configuring IBM FlashSystem 9500 and its parameters. This document also describes the required steps to configure the server that hosts the EHR application. To complete these tasks, you must be knowledgeable of IBM FlashSystem 9500 and Epic applications. This Blueprint provides the following information: A solutions architecture and the related solution configuration information for the following essential components of software and hardware: Detailed technical configuration steps for configuring IBM FlashSystem 9500 Server configuration details for Caché database and Epic applications.